2019
DOI: 10.4314/sajas.v49i2.18
|View full text |Cite
|
Sign up to set email alerts
|

Carcass and meat quality attributes of Malawi Zebu steers fed <i>Vachellia polyacantha</i> leaves or <i>Adansonia digitata</i> seed as alternative protein sources to <i>Glycine max</i>

Abstract: To enhance smallholder beef farmers' capacity to cope with animal feed shortages, especially dietary protein induced by climate change, it is important to evaluate the feeding value of low-cost protein sources naturally available in the environment. The aim of the study was to evaluate carcass and meat quality of Malawi Zebu steers fed diets containing Adansonia digitata (baobab) seed meal or Vachellia polyacantha (white thorn tree) leaf meal as alternative protein sources to Glycine max (soybean) under feedlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Alien invasive plants such as the Acacia species have been introduced in some SADC countries for the provision of timber and tannin extracts [58], but have encroached into rangelands in the smallholder areas [56]. Vachellia karroo and Vachellia polyacantha indigenous invasive species have been incorporated as protein supplements in beef diets and improved growth performance and carcass quality of indigenous cattle [59,60]. Such locally based strategies can increase the rangeland productivity and adaptive capacity for the owners of indigenous cattle genetic resources [57].…”
Section: Cattle Feeding Strategiesmentioning
confidence: 99%
“…Alien invasive plants such as the Acacia species have been introduced in some SADC countries for the provision of timber and tannin extracts [58], but have encroached into rangelands in the smallholder areas [56]. Vachellia karroo and Vachellia polyacantha indigenous invasive species have been incorporated as protein supplements in beef diets and improved growth performance and carcass quality of indigenous cattle [59,60]. Such locally based strategies can increase the rangeland productivity and adaptive capacity for the owners of indigenous cattle genetic resources [57].…”
Section: Cattle Feeding Strategiesmentioning
confidence: 99%
“…Feeding lambs on MKCD and SCD resulted in similar gross margins while using the CD led to high variable costs. Similarly, Chingala et al [ 55 ] reported lower gross margins from steers fed on soybean meal complete diets than in steers fattened by Baobab ( Adansonia digitata ) complete diet and white thorn tree ( Vachelia polyacantha ) leaf meal diet, respectively. The use of MKC in complete lamb diets is a viable option to adopt, especially during periods when the cost of conventional protein sources is expensive due to high demand and limited supplies.…”
Section: Discussionmentioning
confidence: 99%